Activated Ras Signaling Pathways and Reovirus Oncolysis: An Update on the Mechanism of Preferential Reovirus Replication in Cancer Cells - Gong, Jun; Mita, Monica M. (Frontiers in Oncology, 2014)
The development of wild-type, unmodified Type 3 Dearing (T3D) strain reovirus as an anticancer agent has currently expanded to 32 clinical trials (both completed and ongoing) involving reovirus in the treatment of cancer. It has been more than 30 years since the potential of reovirus as an anticancer agent was first identified in studies that demonstrated the preferential replication of reovirus in transformed cell lines but not in normal cells. Later investigations have revealed the involvement of activated Ras signaling pathways (both upstream and downstream) and key steps of the reovirus infectious cycle in promoting preferential replication in cancer cells with reovirus-induced cancer cell death occurring through necrotic, apoptotic, and autophagic pathways. There is increasing evidence that reovirus-induced antitumor immunity involving both innate and adaptive responses also contributes to therapeutic efficacy though this discussion is beyond the scope of this article. Here we review our current understanding of the mechanism of oncolysis contributing to the broad anticancer activity of reovirus. Further understanding of reovirus oncolysis is critical in enhancing the clinical development and efficacy of reovirus.